Boom or Gloom? Examining the Dutch Disease in Two-Speed Economies - Hilde C. Bjørnland; Leif Anders Thorsrud (Norges Bank, 2014)
Traditional studies of the Dutch disease do not account for productivity spillovers between the booming resource sector and other domestic sectors. We put forward a simple theory model that allows for such spillovers. We then identify and quantify these spillovers using a Bayesian Dynamic Factor Model (BDFM). The model allows for resource movements and spending effects through a large panel of variables at the sectoral level, while also identifying disturbances to the commodity price, global demand and non-resource activity. Using Australia and Norway as representative cases studies, we find that a booming resource sector has substantial productivity spillovers on non-resource sectors, effects that have not been captured in previous analysis. That withstanding, there is also evidence of two-speed economies, with non-traded industries growing at a faster pace than traded. Furthermore, commodity prices also stimulate the economy, but primarily if an increase is caused by higher global demand. Commodity price growth unrelated to global activity is less favourable, and for Australia, there is evidence of a Dutch disease effect with crowding out of the tradable sectors. As such, our results show the importance of distinguishing between windfall gains due to volume and price changes when analysing the Dutch disease hypothesis.
hdl:11250/2495971
Keywords: C32; E32; F41; Q33; 330; BDFM; Bayesian dynamic factor model; Dutch disease; resource boom; commodity prices; learning by doing; two-speed economy